CREATIVE ACCOUNTING AND SHAREHOLDERS WEALTH MAXIMIZATION IN LISTED CONSUMER GOODS COMPANIES IN NIGERIA - Olalekan Iredele, Oluwamayowa; Babatunde Adeyeye, Gbadegesin; Babatunde Owoyomi, Ebenezer (Copernican Journal of Finance & Accounting, 2022)
This study examines the effect of creative accounting practices on the shareholders wealth of 90 firm-year observations of ten (10) consumer goods companies listed on the Nigerian Stock Exchange (NSE). Ex post facto research design was adopted using dataset for the period 2011–2019 which were collated from the annual reports and financial statements of the listed consumer goods companies. Four hypotheses were proposed and tested using pooled panel data regression. Findings revealed that frequent changes in inventory valuation method and assets valuation methods respectively have significant effect on shareholders wealth, while frequent changes in depreciation methods and liabilities valuation methods do not significantly affect shareholders’ wealth. The study recommends that external auditors should pay attention to discretionary items in the financial statements in order to ensure that the assumptions used by managers are fair. Regulators should also evaluate the adequacy of policies around inventory and assets valuation while financial analysts and shareholders should note the application and consistency of accounting policies on inventory and assets.